1985
DOI: 10.1152/ajpheart.1985.249.5.h907
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and endocrine effects of potassium in spontaneously hypertensive rats

Abstract: Although potassium is known to lower blood pressure in a number of forms of experimental and human hypertension, the mechanism for this effect remains unclear. We studied several possible mechanisms for this effect in the spontaneously hypertensive rat (SHR). Fourteen-week-old SHR were given 0.5% KCl in the drinking water. This potassium supplement resulted in a 16-mmHg fall in mean arterial pressure and a 22% decrease in peripheral vascular resistance. Plasma potassium increased 0.4 meq/l, while muscle potass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…Along these lines, potassium supplementation was reported earlier to be beneficial in stroke- prone spontaneously hypertensive and in Dahl salt-sensitive rats via reduction of BP. 16,17,29 Nonetheless, in the 2-renin gene model, correction of plasma K ϩ values and metabolic alkalosis also appears to contribute to the prevention of left ventricular and renal hypertrophy, as indicated by the significant correlations obtained between serum K ϩ levels or blood pH and cardiac and renal weight indices (Table 2). One limitation of the study is the rather short duration of potassium supplementation.…”
Section: Wang Et Al Hypokalemia and Cardiac Hypertrophy 551mentioning
confidence: 95%
“…Along these lines, potassium supplementation was reported earlier to be beneficial in stroke- prone spontaneously hypertensive and in Dahl salt-sensitive rats via reduction of BP. 16,17,29 Nonetheless, in the 2-renin gene model, correction of plasma K ϩ values and metabolic alkalosis also appears to contribute to the prevention of left ventricular and renal hypertrophy, as indicated by the significant correlations obtained between serum K ϩ levels or blood pH and cardiac and renal weight indices (Table 2). One limitation of the study is the rather short duration of potassium supplementation.…”
Section: Wang Et Al Hypokalemia and Cardiac Hypertrophy 551mentioning
confidence: 95%
“…Since that time, numerous studies in human [2][3][4][5] and animal models of hyper tension [6][7][8][9] have confirmed the bloodpressure-lowering effects of potassium sup plementation.…”
Section: Introductionmentioning
confidence: 94%
“…They in clude: direct vasodilation; potassium-in duced natriuresis and diuresis, which may be the most important mechanism for lowering blood pressure in DOCA-salt animals: re duced vascular reactivity, and alterations in sympathetic nervous system activity. Work man and Palier [9] have shown that potas sium supplementation neither increases so dium excretion in SHR nor does it cause any change in plasma renin activity. They also saw no substantial differences in blood pres sure responses to angiotensin II or norepi nephrine administration.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…For instance, increasing plasma potassium by 0.4 mM decreased blood pressure by 16 mm Hg in SHR. 21 In another study, a tenfold increase in dietary potassium was used to lower blood pressure in hypertensive rats. 13 In our study potassium intake increased fourfold and did not result in an increase in plasma potassium, which may explain the lack of an effect on blood pressure of the high potassium intake in our study.…”
Section: Figure 3 Systolic Blood Pressure Of the Wky And Shr As A Fumentioning
confidence: 99%